Synthesis and Structural Characterization of a Schiff Base Azamacrocyclic Nickel(II) Complex - Bi, Jian-Hong; Li, Bai-Zhong; Dong, Hua-Ze (Asian Journal of Chemistry, 2013)
Schiff base azamacrocyclic nickel(II) complex [NiL]·SCN·SO4·H2O (L = 5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazamacrocyclic-4,11-diene) was synthesized and characterized by IR spectra and single-crystal X-ray diffraction analysis. The crystal belongs to triclinic, space group P-1 with unit cell parameters: a = 7.2678(11)Å, b = 8.9998(13)Å, c = 19.513(2)Å, a = 84.1430(10)º, b = 87.005(2)º, g = 67.3480(10)º, V = 1171.6(3)Å3, Z = 2, Mr = 511.32, Dc = 1.449 Mg/cm3, μ = 1.043 mm-1, F(000) = 542, T = 298(2) K, R = 0.0375, wR = 0.0882 for 6103 reflections with I > 2(I). In the molecular structure unit, the center nickel(II) ion is four-coordinated in a slightly distorted plane square geometry.